The Lady of the Dugout - Marks, Martin (Treasures 5: The West (1898-1938), 2011)
Although this virtually unseen 5-reeler from 1918-produced, written by and starring real-life Western bandit Al Jennings-deserves revival for its curiosity value alone, it also proves highly entertaining. Jennings' odd career took him from frontier bank robber to prison inmate, then winner of a Presidential pardon from Theodore Roosevelt. After an unsuccessful run in 1914 for governor of Oklahoma, the state that had put a bounty on him, Jennings took to the religious lecture circuit, using his life as a lesson. "Based on absolute facts", as one reviewer optimistically noted, "Lady of the Dug-Out" makes Jennings out as a Western Robin Hood who gallantly bestows bank loot on an impoverished mother and child living in a half-buried sod house (the "dug-out"). Al Jennings and his brother Frank ought to have been far too old in 1918 to impersonate their wild youth, but they still look mighty sinewy here. The entire film has a disarming charm and apparently effortless authenticity unknown in the Western genre since the 'teens. [www.bampfa.berkeley.edu]